The Concept of State Defense in the Millennial Era and in the midst of the Pandemic Covid -19 According to the Foundation of State Defense in Article 27 Paragraph (3) and Article 30 Paragraph (1) of UUD 1945 (by PPWK activities National Insight Education - Ragil Ira Mayasari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Based on Article 27 Paragraph (3) and Article 30 Paragraph (1) of UUD 1945 in increasing the sense of State Defense, Bakesbangpol Mojokerto City plays an active role among high school students in Mojokerto City with the PPWK activity "Education Center with National Insights"The method used in this research is using the juridical empirical method. What is meant by Juridical Empirical is that in analyzing problems, it is done by combining legal materials (which are secondary data) and primary data obtained from the field. As a scientific activity, this research is not based on reviewing only one discipline, but is based on the perspective of the relevant educational disciplines. However, although the research carried out uses the perspective of educational disciplines, it is still a legal research where in this study the perspective of the discipline of law is only used as a tool in its implementation. With the research conducted for ± 10 months, namely in February-November, significant results were obtained where the data was obtained from the comparison of the average student answers through the pre-test and post-test. So it can be concluded, that with the PPWK activity "National Insights Education Center" carried out in high schools in Mojokerto City, it can help realize the Concept of State Defense in the Millennial Era and in the midst of the Covid 19 Pandemic According to the Foundation of State Defense in Article 27 Paragraph (3) and Article 30 Paragraph (1) of UUD 1945.